Theology and society in the second and third centuries of the Hijra. a history of religious thought in Early Islam - Ess, Josef van. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2017)
Theology and Society is the most comprehensive study of Islamic intellectual and religious history, focusing on Muslim theology. With its emphasis on the eighth and ninth centuries CE, it remains the most detailed prosopographical study of the early phase of the formation of Islam. Originally published in German between 1991 and 1995, Theology and Society is a monument of scholarship and a unique scholarly enterprise which has stood the test of time as an unparalleled reference work.